THE SITUATED HINTERLANDS OF ONLINE GAMING PRACTICES - Cumming, David; Rogerson, Melissa Jane (AoIR Selected Papers of Internet Research, 2019)
Previous work has established the existence and research interest of a “digital hinterland” (Rogerson, Gibbs & Smith, 2017) – online practices that support and frame people’s engagement with a hobby. In this paper, we extend the notion of the hinterland from digital-only practices to consider how online-gaming practices are framed by engagement in activities held in material spaces. Looking at the esports bar spectatorship experience, we describe how attendance substantiates and supports fans’ relationship with their fandom and with other fans. We draw on existing literature about esports experiences, practices of offline gaming hobbyists, and sports and media tourism, to show that shared time and place, attendance, and their contribution to an individual’s gaming capital (Consalvo, 2007; Walsh & Apperley, 2009) are important elements of this situated hinterland.